Perceptions and experiences of community-based social accompaniment for stunting prevention among vulnerable mothers in Garut, Indonesia: A qualitative study - Authors: Asaas Putra, Jenny Ratna Suminar, Agus Rusmana, Henny Sri Mulyani (Journal of Daoist Studies, 2026)
Background: Stunting continues to be a multidimensional public health crisis in Indonesia. Conditional cash transfer (CCT) programs, such as the Family Hope Program (PKH), offer financial assistance, but their effect on reducing stunting is largely determined by the social support provided by the primary health care networks at the community level. Objectives: To examine the perceptions and experience of social accompaniment among vulnerable mothers and primary healthcare actors in Garut Regency, a district that has been very successful in reducing stunting prevalence from 27.3% in 2022 to 14.2% in 2024, surpassing provincial and national targets. Methods: This research is a qualitative case study which was conducted in Garut Regency from January 2025 to March 2026. The COREQ reporting guidelines have been followed. In-depth interviews and participatory observations were conducted with 13 informants consisting of PKH facilitators, primary healthcare workers and vulnerable beneficiary mothers. The data were analysed using a thematic analysis. Results: Three main themes were identified. First, PKH facilitators act as cultural brokers by translating health communication into the local Sundanese cultural and religious context. This successfully bridges the gap between primary healthcare providers and the community. Secondly, social accompaniment is limited by significant structural and cultural barriers, including fragmented health data and entrenched sanitary myths. Third, the accompaniment process transforms perceptions of PKH from a financial assistance to a catalyst for behavioural change and health empowerment at household level. Conclusions: Community-based social accompaniment is essential to translating national stunting policies into local practice and has been a major contributor to Garut’s impressive stunting decline. Primary healthcare systems need to formally integrate social adaptive community accompaniment into stunting interventions. We recommend collaborative models between general practitioners, midwives and social facilitators to ensure culturally resonant and sustainable stunting prevention. Stunting; Cash transfer; Social support; Primary health care; General practice; Qualitative study; Indonesia